1935
DOI: 10.1002/recl.19350541105
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium in the system H2O‐MgBr2

Abstract: The solubility of magnesium bromide in water has been determined by Etard I ) , Menschutkin 2 ) , Mylius and Funk 3 ) and Panfiloff 1). The data of Etard appear to be erroneous being nearly ten percent higher than the values found by Menschutkin and Mylius and Funk.The solubility determinations of Menschutkin extend from -10' to 160' C; the solid phase in equilibrium with the solutions over this range of temperature being magnesium bromide hexahydrate, MgBr, . 6 HzO. The salt employed by Menschutkin was prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1938
1938
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The discovery of decahydrate in magnesium dichloride hydrates may imply the existence of decahydrates in magnesium bromide and magnesium iodide. These were postulated on the basis of chemical analyses many years ago (Panfilowa, 1894;Getman, 1935), although their existence has been questioned in the recent literature (Hennings et al, 2013). Hennings et al (2013) concluded that the highest hydration number for both magnesium bromide and magnesium iodide is 9 based on their crystallization experiments.…”
Section: Structure Of Mgcl 2 á10d 2 Omentioning
confidence: 99%
“…The discovery of decahydrate in magnesium dichloride hydrates may imply the existence of decahydrates in magnesium bromide and magnesium iodide. These were postulated on the basis of chemical analyses many years ago (Panfilowa, 1894;Getman, 1935), although their existence has been questioned in the recent literature (Hennings et al, 2013). Hennings et al (2013) concluded that the highest hydration number for both magnesium bromide and magnesium iodide is 9 based on their crystallization experiments.…”
Section: Structure Of Mgcl 2 á10d 2 Omentioning
confidence: 99%
“…MgBr 2 Á10H 2 O is reported as the most water-rich magnesium bromide solid phase at low temperatures in the solid-liquid phase diagram (Panfilowa, 1894;Getman, 1935). However, composition data were derived from chemical analyses, which were difficult to perform with the unstable crystals at ambient temperature.…”
Section: Nonahydrates Of Mgbr 2 and Mgimentioning
confidence: 99%